Student Challenges in Translating Literary Works - Cholifah, Salwaa Ulayya Laily; Heriyanto, Eko; Setiawan, Anjar (UM Purwokerto Press, 2025)
Literary translation is a challenging process that requires linguistic skills, cultural sensitivity, and creative interpretation. The distinctive characteristics of literary writings, including figurative language, cultural references, and the emotional profundity of a literary work, maybe diminished throughout the translation process into another language. This study seeks to identify and examine translators' challenges in maintaining meaning across languages in literary texts. The study employed a descriptive quantitative methodology, with 30 professional literary translators as participants. Data were gathered via surveys targeting particular translation challenges associated with idiomatic language, cultural context, and stylistic fidelity. A structured questionnaire comprising closed and scaled items was utilized as the instrument. The results indicate that the predominant challenges faced pertain to sustaining cultural relevance and achieving stylistic similarity. This study finds that good literary translation necessitates a meticulous equilibrium between literal fidelity and creative adaptation to maintain the original work's meaning and emotional resonance.